Epidemiology of injuries connected with dance: a critical review on epidemiology - Giuseppe Rinonapoli; Marta Graziani; Paolo Ceccarini; Cristina Razzano; Francesco Manfreda; Auro Caraffa (Medicinski glasnik, 2020)
The aim of this review was to identify all types of injuries connected to the gestures of dancers and understand the associated biomechanical patterns. This is the first step in the definition of a prevention program that lacks in this kind of athletic activity. A search of Medline/PubMed, EMBASE, and the Cochrane database from 1990 to 2019 using the search terms ‘‘dance and injuries’’ and ‘‘dance and injuries and epidemiology’’ initially resulted in 601 citations. A total of 16 articles were eligible for a review. All health problems that lead to stop the activity of a dancer are classified as "dancer's injuries". They were divided in acute and overuse injuries, the first being traumatic and the latter ones microtraumatic. The anatomical region most affected by injuries in dance was clearly the ankle and foot. It can be inferred that professional and pre-professional dancers had a higher prevalence of back injuries in comparison to amateur dancers, while amateurs suffered more frequently from hip/groin/thigh injuries. Doctors, teachers, sport trainers and dancers themselves, all those who contribute to the dancer's performance, should know the most prevalent dancers’ injuries. Moreover, they should know the prevention procedures, in order to minimize the risk of injury and recurrences.
Keywords: dancer; joint; back; ankle; knee